2014
DOI: 10.4322/acr.2014.028
|View full text |Cite
|
Sign up to set email alerts
|

Advanced small-cell ovarian carcinoma, hypercalcemic type: a challenging therapeutic entity

Abstract: Small-cell ovarian carcinoma (SCOC) is a rare and aggressive neoplasia, predominantly affecting young women who are frequently first diagnosed with advanced stage disease. Platinum-based chemotherapy (ChT) can provide high response rates and rapidly ameliorate symptoms in this scenario. However, progression after chemotherapy usually occurs quickly, leading to high mortality rates. In addition, ChT complications, such as tumor lysis syndrome (TLS) can also occur, jeopardizing the patient’s outcome. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Multivariate analyses have demonstrated that tumor stage at diagnosis is the most significant determinant of prognosis ( Witkowski et al, 2016 ). Reports demonstrate a five-year overall survival of 33–55 % in patients with stage I disease ( Witkowski et al, 2016 , Young et al, 1994 ) and as low as 10 % in advanced stage patients ( Bitton et al, 2014 , Harrison et al, 2006 ). Witkowski et al evaluated determinants of survival and found that after tumor stage, treatment modality was the second most significant factor impacting survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate analyses have demonstrated that tumor stage at diagnosis is the most significant determinant of prognosis ( Witkowski et al, 2016 ). Reports demonstrate a five-year overall survival of 33–55 % in patients with stage I disease ( Witkowski et al, 2016 , Young et al, 1994 ) and as low as 10 % in advanced stage patients ( Bitton et al, 2014 , Harrison et al, 2006 ). Witkowski et al evaluated determinants of survival and found that after tumor stage, treatment modality was the second most significant factor impacting survival.…”
Section: Discussionmentioning
confidence: 99%
“…Small cell carcinoma of the ovary hypercalcemic type (SCCOHT) is a rare gynecologic malignancy with most literature limited to case report documentation ( Bitton et al, 2014 , Tewari et al, 1997 ). SCCOHT tends to present in early adulthood ( Witkowski et al, 2016 , Callegaro-Filho et al, 2016 ) though pediatric cases have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…193 One of the most common gynecological cancers in RTPS2 is small-cell carcinoma of the ovary, hypercalcemic type (SCCOHT), which is reported to have demonstrated five-year OS rates of 33%-55% in patients with stage I disease, 194,195 and ≤10% in advanced stage patients. 196,197 Since ≥40% of women with SCCOHT may have a SMARCA4 GPV, RTPS2 may be suggested when bilateral SCCOHT is detected at a young age. 198,199 As SCCOHT affects females aged 5-46 years, abdominalpelvic ultrasound is the recommended method of surveillance for individuals with RTPS2, particularly among children and teenagers.…”
Section: Smarca4mentioning
confidence: 99%